Asymmetric Magnetohydrodynamic Propulsion for Oil–Water Core Annular Flow Through Elbow - Chengming Wang; Zezhong Jia; Lei Yang; Yongqi Xu; Jinhao Zhao; Shihui Jiao; Hao Ma; Ruofan Shen; Erjun Liang; Weiwei Zhang; Yanyan Liu; Baojun Li (Applied Sciences, 2025)
The use of oil–water rings has become an emerging, effective, and energy-saving method of transporting heavy oil. Maintaining the shape of the oil–water ring and preventing rupture during the transport of heavy oil are of great scientific significance in oil–water annular flow transportation. To ensure the oil–water ring passes smoothly through the elbow without rupture, this article proposes an asymmetrical magnetohydrodynamic (MHD) propulsion method to utilize the significant difference between the conductivity of heavy oil and electrolyte solution to achieve an accelerating effect on the outer water ring. The magnetohydrodynamic device designed by this method can generate a magnetic field and provide Lorentzian magnetic force to achieve the asymmetric acceleration of the oil and water rings, to homogenize the water ring velocity on the inner and outer elbows, to push the deviated oil core back to the center of the pipeline, and to repair the rupture of the water film. The flow state of the oil–water ring in the bend pipe under the joint action of the electric field and magnetic field is simulated by a differential MHD thick oil simulation flow model, which confirms that the device can realize the repair of the oil–water ring flow at the bend pipe and ensure that the oil–water ring flow passes through the bend pipe stably. Meanwhile, the effects of coil current, electrode plate voltage, and the conductivity of electrolyte solution on the morphology and velocity of the oil–water ring in the elbow are investigated. In addition, the role of the device in maintaining the morphology under different gravitational conditions is investigated. These results provide a reference design for related devices and offer a new approach to heavy oil transportation.